2021
DOI: 10.3390/pathogens10121634
|View full text |Cite
|
Sign up to set email alerts
|

Understanding COVID-19 Pathogenesis: A Drug-Repurposing Effort to Disrupt Nsp-1 Binding to Export Machinery Receptor Complex

Abstract: Non-structural protein 1 (Nsp1) is a virulence factor found in all beta coronaviruses (b-CoVs). Recent studies have shown that Nsp1 of SARS-CoV-2 virus interacts with the nuclear export receptor complex, which includes nuclear RNA export factor 1 (NXF1) and nuclear transport factor 2-like export factor 1 (NXT1). The NXF1–NXT1 complex plays a crucial role in the transport of host messenger RNA (mRNA). Nsp1 interferes with the proper binding of NXF1 to mRNA export adaptors and its docking to the nuclear pore com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…As described in previous sections, the multifunctional SARS-CoV-2 Nsp1 interacts directly with the NXF1 and NXT1 proteins of the nuclear pore complex disrupting the nuclear mRNA export machinery and, therefore, inhibiting host gene expression ( Zhang et al., 2021 ). The e-Drug3D database, which contained around 2,000 Food and Drug Administration (FDA)-approved drugs, was used to dock to the structure of the NXF1/NXT1-Nsp1 complex to identify compounds that interfere with the binding of SARS-CoV-2 Nsp1 with NXF1/NXT1 ( Vasudevan and Baraniuk, 2021 ). In this in silico study, the top identified hit was ganirelix, which competitively antagonizes the gonadotropin releasing hormone receptor (GNRHR) ( Vasudevan and Baraniuk, 2021 ).…”
Section: Iav Ns1 and Sars-cov-2 Nsp1 As Targets For Antiviral Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…As described in previous sections, the multifunctional SARS-CoV-2 Nsp1 interacts directly with the NXF1 and NXT1 proteins of the nuclear pore complex disrupting the nuclear mRNA export machinery and, therefore, inhibiting host gene expression ( Zhang et al., 2021 ). The e-Drug3D database, which contained around 2,000 Food and Drug Administration (FDA)-approved drugs, was used to dock to the structure of the NXF1/NXT1-Nsp1 complex to identify compounds that interfere with the binding of SARS-CoV-2 Nsp1 with NXF1/NXT1 ( Vasudevan and Baraniuk, 2021 ). In this in silico study, the top identified hit was ganirelix, which competitively antagonizes the gonadotropin releasing hormone receptor (GNRHR) ( Vasudevan and Baraniuk, 2021 ).…”
Section: Iav Ns1 and Sars-cov-2 Nsp1 As Targets For Antiviral Researchmentioning
confidence: 99%
“…The e-Drug3D database, which contained around 2,000 Food and Drug Administration (FDA)-approved drugs, was used to dock to the structure of the NXF1/NXT1-Nsp1 complex to identify compounds that interfere with the binding of SARS-CoV-2 Nsp1 with NXF1/NXT1 ( Vasudevan and Baraniuk, 2021 ). In this in silico study, the top identified hit was ganirelix, which competitively antagonizes the gonadotropin releasing hormone receptor (GNRHR) ( Vasudevan and Baraniuk, 2021 ). However, authors did not carry out in vitro experimental tests to confirm the antiviral effect of this compound against SARS-CoV-2 ( Vasudevan and Baraniuk, 2021 ).…”
Section: Iav Ns1 and Sars-cov-2 Nsp1 As Targets For Antiviral Researchmentioning
confidence: 99%
See 1 more Smart Citation